Peculiarities about judicial authority in case of international child abduction for the purpose of council Regulation (EC) 2201/2003 - Carrizo Aguado, David (CUADERNOS DE DERECHO TRANSNACIONAL, 2020)
Most of the set of international child abduction cases are a tragic and painful manifestation of a marriage or couple crisis. In this framework, cross-border withholding, in the face of strictly internal situations, has as its distinctive element the displacement or transfer of the minor in charge of the abducer in order to find a different legal system of coverage that is more favorable to his interests. To avoid multiple damages and in order to preserve the best interests of the minor, Council Regulation (EC) 2201/2003 shields competition in this matter in favor of the courts of the minor’s habitual residence. Although, the great diversity of causes underlying child abduction should not be ignored when proposing the most appropriate solution.